NILAI-NILAI BUDAYA DALAM NOVEL 33 SENJA DI HALMAHERA KARYA INTAN ANDARU - Nelly Nelly; Christanto Syam; Antonius Totok Priyadi (Universitas Tanjungpura, 2020)
AbstractThis research is motivated by the importance of the idea of community life in the midst of the turmoil of negative influences in the current modern era which often causes moral degradation in the younger generation. The general problem discussed in this research is about the cultural values found in the North Maluku islands, South Halmahera, which is reflected in novel 33 Senja di Halmahera by Intan Andaru. The results of this study describe cultural values that reflect the relationship between humans and God; the relationship between humans and themselves; the relationship between humans and humans is divided into two, namely: a) relationship with family, and b) relationship with society; and the relationship between humans and nature. The results of this study can be used as an implementation plan for Indonesian language learning class XII high school education units in the 2013 curriculum with Basic Competence (KD) 3.8 Interpreting the author's view of life in the novel being read, and Basic Competence (KD) 4.8 Presenting the results of the interpretation of the author's view.Keywords: Analysis, Cultural Values, 33 Senja di Halmahera